The Effectiveness of Semi Fowler Position 30 Degrees and 45 Degrees on Increasing SPO2 and Respiratory Rate of Lung TB Patients: Literature Review - Padliannor, Hifzhi; Riduansyah, Muhammad; Mahmudah, Rifa’atul; Latifah, Hj (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
Pulmonary TB is a disease caused by Mycobacterium tuberculosis which attacks the respiratory system and often decreases SPO2. Interventions that can be done to reduce shortness of breath and increase SPO2 are by giving a semi-fowler position. To determine the effectiveness of the semi-Fowler's position on increasing SPO2 and breathing patterns in pulmonary TB patients. Research design literature review. Journal criteria were screened based on literature titles, abstracts and keywords that had been determined and sourced from Biomed Central, DOAJ, Pubmed, Elsevier, and EBSCO HOST identified through the Population, Intervention, Comparation, Outcomes and Study Design (PICOS) system approach. The number of articles used for this literature is 12 journals. Pulmonary TB patients experienced an increase in SPO2 and a decrease in shortness of breath after being given the semi-Fowler position intervention. The results of the analysis showed the effectiveness of the semi-Fowler position to increase SPO2 and reduce shortness of breath in pulmonary TB patients. Health facilities can provide interventions regarding the effectiveness of the semi-Fowler's position to increase SPO2 and reduce shortness of breath, besides that it can also be used as a nursing care intervention program in pulmonary TB patients.